El balanced scorecard como herramienta para la toma de decisiones de la gestión empresarial en el Perú. - Montenegro Luciano, Luis Miguel (2011)
In a world dominated by the global economy, we must have a body of knowledge that enables managers of all backgrounds have a working reference frames and use some tools to help man the information management. One such tool, which allows using the information resource more efficiently, quickly and reliably, especially for decisionmaking is the BSC, which is framed within the rapid technological progress that has characterized the last decades of this century. The Balanced Scorecard is an integrated, balanced and strategic measure current progress and provide future direction of the company that allows you to convert vision into action through a coherent set of indicators grouped into four different perspectives, through which you can see the business as a whole. The Balanced Scorecard helps to manage complex information. Whether in a large organization as a small, clear that the latter is more manageable than in the previous case. The truth is that we live in a society where excel, companies better manage their information and processes. Is looking for success the Banco de Crédito BCP seeks to improve its processes in order to provide better quality customer service. The development of the Research: "THE BALANCED SCORECARD AS A TOOL FOR CORPORATE MANAGEMENT IN PERU" main objective is to implement the BSC in the Banco de Credito BCP following the scheme proposed in this paper. Through the development of the Research expects to meet the objectives outlined in the course of your career. With the development of this research work, I hope to make a guide that will serve several purposes, such as provide insight to people who are interested in implementing BSC in your company, what to do, taking into account the aspects that are necessary for implementation. In addition, the Research Project will provide students with a tool to support the development of similar jobs.